The first step is to remember that you can add exponents together. Then move everything into the numerator and add the exponets. this will give you your answer.
(5x^-2)-(3y^-1)
--------------- (original)
(x^-1)+(y^-1)
(5x^-2)+(x^1)-(3y^-1)+(y^1)
(5x^-1)-3 (-2+1=-1, and -1+1=0)
Please simplify.
5x ^-2 - 3y ^-1/
x ^-1 + y ^-1
The 5x is on top and the x^-1 is on the bottom
2 answers
There is no division necessary here? So the final answer is what is @ the bottom?
(5x^-1)-3 (-2+1=-1, and -1+1=0)
(5x^-1)-3 (-2+1=-1, and -1+1=0)